Fungal Diversity Survey Sweden ITS-LSU rDNA - Patrick Fritzson; Björn Bråvander (Uppsala University, 2025)
Project Overview

The project aims to investigate species diversity and variety from a citizen science perspective (more of a random character, i.e., not a strictly scientific research character).

Project Goals

- Investigate species diversity and variety on a larger scale (>1,000 samples)
- Give sequences a "face" = metadata such as environmental data, field images, etc.
- Provide tools for species identification
- Use DNA barcoding of the ITS region
- Be cost-effective
- Be methodologically feasible from fruiting body to analyzed sequence
- Disseminate knowledge about the method


Dataset Description

The dataset contains DNA-barcoded samples of fungal fruiting bodies collected in Sweden. The collection has been mostly random and the selection has primarily been based on the collector's own interest. Collectors are mainly amateur mycologists. Barcoding has been performed on the ITS region and parts of the SSU and LSU regions. Additional observational metadata such as coordinates, images, and environmental descriptions are linked to the Swedish Observation System for each respective sample.This dataset was published via the SBDI ASV portal. (https://asv-portal.biodiversitydata.se/)
Keywords: Occurrence; Observation; OCCURRENCE; Biological Sciences; Biologi